2021
DOI: 10.3390/ijms22042005
|View full text |Cite
|
Sign up to set email alerts
|

Another Weapon against Cancer and Metastasis: Physical-Activity-Dependent Effects on Adiposity and Adipokines

Abstract: Physically active behavior has been associated with a reduced risk of developing certain types of cancer and improved psychological conditions for patients by reducing anxiety and depression, in turn improving the quality of life of cancer patients. On the other hand, the correlations between inactivity, sedentary behavior, and overweight and obesity with the risk of development and progression of various cancers are well studied, mainly in middle-aged and elderly subjects. In this article, we have revised the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 254 publications
(277 reference statements)
0
10
0
Order By: Relevance
“…However, the exact link between VASP and cancer is still not entirely clear. According to current knowledge, it is known that most adipokines are capable of promoting tumour progression mainly by enhancing the proliferation and migration of tumour cells as well as inflammatory pathways [ 94 , 95 ]. Another mechanism is the participation of these proteins in anti-apoptotic pathways, which may consequently lead to the formation of cancer metastases [ 93 , 96 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the exact link between VASP and cancer is still not entirely clear. According to current knowledge, it is known that most adipokines are capable of promoting tumour progression mainly by enhancing the proliferation and migration of tumour cells as well as inflammatory pathways [ 94 , 95 ]. Another mechanism is the participation of these proteins in anti-apoptotic pathways, which may consequently lead to the formation of cancer metastases [ 93 , 96 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the course of both obesity and carcinogenesis, changes in the metabolic profile of adipose tissue have been observed [ 23 , 24 , 25 ]. This can lead to increased synthesis and secretion of many bioactive compounds, such as hormones, adipokines, inflammatory cytokines, and growth factors [ 26 , 27 , 28 ]. To date, more than 600 adipokines have been discovered.…”
Section: Discussionmentioning
confidence: 99%
“…Several circulating miRNAs, both singularly and grouped in signatures, have been associated with cancer development risk, detection and progression [13]. In parallel, many studies have demonstrated that regular PA reduces the global risk of developing a cancer as well as improves prognosis and reduces the risk of metastasis and side effects of the therapy in subjects treated for primitive tumor [17,94,95]. However, the impact of PA on circulating miRNAs associated with cancer is mostly neglected, as recently reviewed in [21].…”
Section: Discussionmentioning
confidence: 99%
“…Physical inactivity (PI) is the fourth leading cause of death (5.5% of deaths globally) after hypertension, cigarette smoking and hyperglycemia and just before obesity and overweight [16]. PI independently associates with an increased incidence of cancers in general and specifically for certain tumors (e.g., colorectal, lung, breast, prostate, ovarian, endometrial and esophageal) [17]. The net energy surplus consequent to the sedentary behavior is the underlying cause of the onset of these diseases [18].…”
Section: Introductionmentioning
confidence: 99%